2001
DOI: 10.1002/ldr.441
|View full text |Cite
|
Sign up to set email alerts
|

Gardening to reduce hazard: urban agriculture in Tanzania

Abstract: Urban agriculture is an illegal activity in most African towns and cities, as it is seen to be competing with other, higher value, urban land uses. Despite this, food production occurs throughout the African urban environment and is crucial to the urban economy; providing employment, food security and investment opportunity for a large proportion of the urban population. Urban agriculture also adds value to urban land, bringing unused land into production, reversing degradation and improving the urban landscap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Food production systems can also recycle urban plant waste into mulch, which further decomposes and creates organic matter in the soil; for example, urban food producers in Belem, Brazil use waste from a local tree as a form of fertiliser (Madaleno 2000). Finally, food production can also capture water in flood‐prone areas, reducing hazard events as shown in the example of Dar es Salaam, Tanzania (Howorth et al . 2001).…”
Section: Peri‐urban Livelihoods and Food Production Landscapesmentioning
confidence: 99%
“…Food production systems can also recycle urban plant waste into mulch, which further decomposes and creates organic matter in the soil; for example, urban food producers in Belem, Brazil use waste from a local tree as a form of fertiliser (Madaleno 2000). Finally, food production can also capture water in flood‐prone areas, reducing hazard events as shown in the example of Dar es Salaam, Tanzania (Howorth et al . 2001).…”
Section: Peri‐urban Livelihoods and Food Production Landscapesmentioning
confidence: 99%
“…Recent studies have shown that UPA supplies 10-90% of fresh vegetables, up to 70% of meat and up to 100% of eggs on city markets (Maxwell 1995;Madaleno 2000;Cofie et al 2003;Drechsel et al 2005). The proportion of urban households involved in UPA varies from 10 to 57% (Ellis and Sumberg 1998;Howorth et al 2001;Asomani-Boateng 2002;Cofie et al 2003) and so does production intensity and resource use efficiency. Sometimes, high levels of inputs used in the vicinity of human settlements have been reported to cause serious problems to human health and the environment (Ezedinma and Chukuezi 1999;Howorth et al 2001;Asomani-Boateng 2002;Matagi 2002;Binns et al 2003;Bryld 2003;Cofie et al 2003;Drechsel et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…At the present time, we can notice that urban agriculture in Mahajanga is not considered as illegal, as it was the case in other countries like Tanzania (Howorth et al, 2001), but it is totally ignored by local authorities, as it was non-existent in spatial and human occupation. With the increasing interest for this type of agriculture (Cissé et al, 2005;Van Veenhuizen, 2006), and especially for vegetable production (Kahane et al, 2005), this attitude could well change in the years to come.…”
Section: Discussionmentioning
confidence: 94%